Geochemical investigation of the galvanic effects during oxidation of pyrite and base-metals sulfides. (January 2017) - Chopard, Aurélie; Plante, Benoît; Benzaazoua, Mostafa; Bouzahzah, Hassan; Marion, Philippe
Abstract: Predicting the water quality at mine sites is of significant importance for developing mines with respect for the environment. Acid mine drainage (AMD) occurs when sulfides are in contact with oxygen and water, and several parameters and mechanisms influence final drainage quality. Galvanic interactions influence the reactivity of sulfide minerals, which act as semi-conductors. These galvanic interactions have been insufficiently studied in the context of AMD generation. In this study, the influence of pyrite on the reactivity of sphalerite and chalcopyrite was investigated. Five blends, comprised of free grains of quartz/pyrite, quartz/chalcopyrite, quartz/sphalerite, quartz/pyrite/chalcopyrite, and quartz/pyrite/sphalerite, were subjected to geochemical testing. Five weathering cells were monitored over a 200-day period during which they were leached twice weekly. Leachates were analyzed for pH, Eh, electrical conductivity, and sulfate and metal concentrations. The results of these analyses showed that galvanic interactions occurred between free sulfide grains. Pyrite was galvanically protected over the full testing period in the quartz/pyrite/chalcopyrite blend, and partially protected in the quartz/pyrite/sphalerite blend. Moreover, the release of Cu from chalcopyrite and Zn, Mn, and Cd from sphalerite was accelerated in the presence of pyrite. This work provides a better understanding of the influence of pyrite on chalcopyrite and sphalerite reactivity by highlighting the galvanic effects. In the future, to improve the reliability of AMD prediction tests, galvanic interactions should be considered in both the prediction of the acid generation potential and the estimation of metal and metalloid release rates. Highlights: A geochemical investigation of galvanic interactions is proposed. Pyrite is galvanically protected upon contact with chalcopyrite or sphalerite. Sphalerite and chalcopyrite show higher reactivity rates in the presence of pyrite.